Evaluation of the pathological manifestations of the Rio Negro building in Anápolis-Goiás. - Teixeira, Guilherme Henrique; da Silva, Juliano Rodrigues; Chaveiro Alves, Eder (Revista ALCONPAT, 2022)
This paper shows the application of the methodologies GDE (Degree of Deterioration of the Structure) and GUT (Severity, Urgency and Tendency) quantifying the pathological manifestations and determining the points of greatest need for maintenance. Thus, a quantitative perspective was applied with the application of the mentioned methodologies and after building inspections and a visual analysis with photographic record, notes and mappings the methodologies were applied and it was obtained that most of the pathological manifestations that occur in the structure of the building have humidity as origin, resulting in efflorescence, wounds or infiltration. Thus, this work defined the points that need priority, directing measures that can later be taken. The methodologies proved to be efficient and important for decision making.